MicroRNA-522-3p plays an oncogenic role in glioblastoma through activating Wnt/β-catenin signaling pathway via targeting SFRP2. Issue 2 (13th January 2021) - Zhang, Lingdang; Zhang, Peng; Tan, Yun; Feng, Qinglin; Zhao, Rui
Abstract : Background: Increasing studies have suggested that microRNAs (miRNAs) contribute to the occurrence and development of glioblastoma. MiR-522-3p is a novel miRNA, which has been found to modulate tumorigenesis and tumor progression. However, its pathological role and functional mechanism in glioblastoma remain elusive at present. Method: The miR-522-3p expression in glioblastoma and adjacent normal tissues, human fetal astrocyte HA1800, and glioblastoma cell lines was detected by reverse transcription-PCR. The proliferation, migration, and invasion were detected through Cell Counting Kit-8 (CCK8) and Transwell assay, and apoptosis was calculated through flow cytometry. The downstream target of miR-522-3p was analyzed through bioinformatics, and the correlation between miR-522-3p and secreted frizzled-related protein 2 (SFRP2) was verified through dual-luciferase reporter assay and RNA immunoprecipitation (RIP) experiment. Besides, western blot was conducted to test the level of SFRP2 and the Wnt/β-catenin pathway. Results: MiR-522-3p was overexpressed in glioblastoma tissues compared with that in normal tissues, and the inhibition of miR-522-3p reduced cell proliferation, migration, and invasion and promoted apoptosis in glioblastoma. Bioinformatics revealed that SFRP2 was an essential downstream target of miR-522-3p, and it inhibited the malignant biological behaviors induced by miR-522-3p and inactivated the Wnt/β-catenin pathway. Conclusion: MiR-522-3p is an oncogene in glioblastoma by targeting SFRP2 through the Wnt/β-catenin pathway. Abstract : Supplemental Digital Content is available in the text.